Overview and risk factors for postcraniotomy surgical site infection: A four-year experience. Issue 1 (31st January 2022) - Corsini Campioli, Cristina; Challener, Douglas; Comba, Isin Y.; Shah, Aditya; Wilson, Walter R.; Sohail, M. Rizwan; Van Gompel, Jamie J.; O'Horo, John C.
Abstract: Objective: Despite evidence favoring perioperative antibiotic prophylaxis (ABP) use in patients undergoing craniotomy to reduce rates of surgical site infections (SSIs), standardized protocols are lacking. We describe demographic characteristics, risk factors, and ABP choice in patients with craniotomy complicated with SSI. Design: Retrospective case series from January 1, 2017, through December 31, 2020. Setting: Tertiary-care referral center. Patients: Adults who underwent craniotomy and were diagnosed with an SSI. Methods: Logistic regression to estimate odds ratios and 95% confidence intervals to identify factors associated with SSIs. Results: In total, 5, 328 patients undergoing craniotomy were identified during the study period; 59 (1.1%) suffered an SSI. Compared with non-SSI cases, patients with SSI had a significantly higher frequency of emergency procedures: 13.5% versus 5.8% ( P = .02; odds ratio [OR], 2.52; 95% confidene interval [CI], 1.10–5.06; P = .031). Patients with SSI had a higher rate of a dirty (5.1% vs 0.9%) and lower rate of clean-contaminated (3.3% vs 14.5%) wound class than those without infection ( P = .002). Nearly all patients received ABP before craniotomy (98.3% in the SSI group vs 99.6% in the non-SSI group; P = .10). Combination of vancomycin and cefazolin as dual therapy was more prevalent in the group of patients without infection (n = 1, 761, 34.1%) than those with SSI (n = 4, 6.8%) ( P < .001), associated with decreased odds for SSI (OR, 0.17; 95% CI, 0.005–0.42; P ≤ .001). Conclusions: SSI are frequently seen after an emergent neurosurgical procedure and a dirty wound classification. Combination of prophylactic cefazolin and vancomycin is associated with decreased risk for SSI.